Adsorption And Desorption Of Oxytetracycline Hydrochloride On Modified Activated Carbon - Zukfflay @ Zulkifli, Mohammad Hafeez (Universiti Sains Malaysia, 2017)
Adsorption of Oxytetracycline hydrochloride (OTC-HCl) onto commercialize activated carbon that been modified by using Cu(NO2)3 was investigated through batch adsorption process. The modified activated carbon (M.AC) shown the optimum performance at 1.00 Wt %. The effects of the various parameters, such as pH, initial concentration from 5 to 25 mg L-1 and temperature (30,40 and 50) oC was investigated. From the result the adsorption capacity is decreased when increasing the temperature. The highest adsorption capacity was at T=30oC at concentration 25 mg L-1. Langmuir and Freundlich isotherms were used to analyzed data at different temperatures. Its shown that, the Langmuir isotherms almost fits with the experimental data with R2 almost greater than 0.9. Adsorption kinetics data were analyzed using pseudo-first-order and pseudo-second-order. As a result, the adsorption was best fitted by pseudo-second-order kinetics. The adsorption thermodynamics studied was be done to obtained thermodynamics parameters. The sample of adsorption that give optimum condition were characterized using Fourier transformed infrared meanwhile for the modified activated carbon were characterized using Brunauer-Emmett-Teller and Thermal gravimetric analysis. The reusability study of M.AC as adsorbent revealed that it can be reused for several cycles for adsorption-desorption process before the performance of the process reduced below than out targeted.